American Encounters with Nazism: Sources of Early Experiences with the Hitler Movement. - Triolo, Victor (Spring;Library Science., 1997)
Keywords: dept.ils; faculty_collection; sabbatical_report

Incorporation of Pome Fruit Germplasm Inventory into the Grin Database System. - Triolo, Victor (1994)
Keywords: dept.ils; faculty_collection; sabbatical_report

Film Quotations; 11,000 Lines Spoken on Screen. - Nowlan, Gwendolyn Wright (1993)
Keywords: dept.ils; faculty_collection; sabbatical_report

Doctoral Program. - Disbrow, Nancy (1990)
Keywords: dept.ils; faculty_collection; sabbatical_report

We'll Always Have Paris: The Definitive Guide to Great Lines from the Movies - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (HarperCollins Publishers, 1995)
Keywords: Motion pictures; Quotations; maxims; etc; dept.ils; dept.mat; faculty_collection

The Films of the Eighties: A Complete, Qualitative Filmography to Over 3400 Feature-Length English Language Films, Theatrical and Video-Only, Released Between January 1, 1980, and December 31, 1989 - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland & Co., 1991)
Keywords: Catalogs; Motion pictures; dept.ils; dept.mat; faculty_collection

Library Science Research, 1974-1979 - Magnotti, Shirley (Whitson Pub. Co., 1982)
Keywords: Bibliography; Bibliography; Dissertations; Academic; Canada; Library science; United States; dept.ils; faculty_collection

Master's Theses in Library Science, 1970-1974 - Magnotti, Shirley (Whitston Pub. Co., 1976)
Keywords: Bibliography; Bibliography; Dissertations; Academic; Canada; Library science; United States; dept.ils; faculty_collection

Ehanna Woyakapi; History and Culture of the Sisseton Wahpeton Sioux Tribe of South Dakota - Blackthunder, Elijah; Johnson, Norma; Pronovost, Muriel; O'Connor, Larry (Sisseton Wahpeton Sioux Tribe, 1975)
Keywords: History; History; Wahpeton Indians; Sisseton Indians; dept.ils; faculty_collection

Interpreting and Negotiating Licensing Agreements: A Guidebook for the Library, Research, and Teaching Professions - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1999)
Keywords: Handbooks; manuals; etc; Handbooks; manuals; etc; Teachers; License agreements; Popular works; Librarians; United States; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1999)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

How to Use the Library: A Reference and Assignment Guide for Students - Ferro, Frank; Lushington, Nolan (Greenwood Press, 1998)
Keywords: Bibliography; Catalogs; Juvenile literature; Juvenile literature; Library research; Juvenile literature; Reference sources; Reference books; United States; dept.ils; faculty_collection

Technology and Copyright Law: A Guidebook for the Library, Research, and Teaching Professions - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1997)
"Explains the intent of copyright law, how it developed, and where it is headed; provides guidance for making copyright decisions; and discusses the electronic classroom and international copyright agreements."
Keywords: Fair use (Copyright); Law and legislation; United States; United States; Information services; United States; Library legislation; dept.ils; faculty_collection

Library Patrons and the Law - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1995)
Keywords: Censorship; Library legislation; United States; United States; Civil rights; United States; Libraries; United States; Privacy; Right of; dept.ils; faculty_collection

Maintaining the Privacy of Library Records: A Handbook and Guide - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1994)
Keywords: Confidential communications; Library records; United States; dept.ils; faculty_collection

Libraries & Copyright Law - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1993)
Keywords: Fair use (Copyright); Photocopying; United States; United States; Photocopying services in libraries; dept.ils; faculty_collection

Library Employment Within the Law - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1993)
Keywords: Legal status; laws; etc.; Librarians; United States; United States; Library employees; dept.ils; faculty_collection

Feminist Thought in American Librarianship - Baum, Christina D. (McFarland, 1992)
Keywords: Social aspects; United States; United States; Feminism; United States; Libraries and society; United States; Library administration; United States; Library science; United States; Women librarians; Women in library science; dept.ils; faculty_collection

An Introduction to Using the Internet at Southern Connecticut State University - Bretthauer, David; Drew, Christine (1992)
Keywords: dept.ils; faculty_collection

The Connecticut Legal Research Handbook - Cheeseman, Lawrence; Bielefield, Arlene G. (Connecticut Law Book Co., 1992)
Keywords: Connecticut; Handbooks; manuals; etc; Legal research; dept.ils; faculty_collection

Evaluating Library Buildings: Principles and Procedures for Post-Occupancy Evaluation - Kusack, James M. (Connecticut State Library, 1991)
Book Title: Evaluating library buildings : principles and procedures for post-occupancy evaluation Place: Hartford, Conn.
Keywords: Evaluation; Library architecture; Library buildings; United States; dept.ils; faculty_collection

The Design and Evaluation of Public Library Buildings - Lushington, Nolan; Kusack, James M. (Library Professional Publications, 1991)
Keywords: Evaluation; Library buildings; Library architecture; Public libraries; dept.ils; faculty_collection

Educators Guide to Patents and Inventions - Prostano, Emanuel T.; Prostano, Joyce S. (In-Time Publications, 1990)
Keywords: Handbooks; manuals; etc; Patents; dept.ils; faculty_collection

School Library Media Programs: Success in the 90's - Prostano, Emanuel T.; Prostano, Joyce S. (In-Time Publications, 1989)
Keywords: School libraries; Media programs (Education); dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1987)
Keywords: School libraries; dept.ils; faculty_collection

Unions for Academic Library Support Staff: Impact on Workers and the Workplace. - Kusack, James M. (1986)
Keywords: Administration; Libraries and labor unions; College employees; Labor unions; Library employees; United States; United States; Academic libraries; United States; Collective bargaining; United States; Labor unions; dept.ils; faculty_collection

The Basic Business Library: Core Resources - Schlessinger, Bernard S. (Oryx Press, 1983)
Keywords: Bibliography; Bibliography; Business; Bibliography; Business libraries; Business libraries; Business; Reference books; dept.ils; faculty_collection

Scientific Management of Library Operations - Dougherty, Richard M.; Heinritz, Fred John (Scarecrow Press, 1982)
Keywords: Library administration; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1982)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1977)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

Andover in the American Revolution: A New England Town in a Period of Crisis, 1763-1790 - Harris, Edward Moseley (Walsworth Pub. Co., 1976)
Keywords: 18th century; Andover (Mass.); Biography; Andover (Mass.); Campaigns; Andover (Mass.); Genealogy; History; Revolution; 1775-1783; United States; dept.ils

School Media Programs: Case Studies in Management, - Prostano, Emanuel T. (Scarecrow Press, 1974)
Keywords: Administration; Case studies; Case studies; Media programs (Education); School libraries; dept.ils; faculty_collection

Law Enforcement; a Selective Bibliography - Prostano, Emanuel T.; Piccirillo, Martin L. (Libraries Unlimited, 1974)
Keywords: Bibliography; Bibliography; Crime; Bibliography; Criminal justice; Administration of; Bibliography; Police; Law enforcement; dept.ils; faculty_collection

Audiovisual Media and Libraries; Selected Readings. - Prostano, Emanuel T. (Libraries Unlimited, 1972)
Keywords: Audio-visual library service; dept.ils; faculty_collection

Users and Uses of the New Haven Free Public Library, July, 1972; a Survey - Schlessinger, Bernard S. (1972)
Keywords: New Haven Free Public Library; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1971)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

School Media Programs: Case Studies in Management, - Prostano, Emanuel T. (Scarecrow Press, 1970)
Keywords: Administration; Case studies; Case studies; Library administration; Case studies; Media programs (Education); School libraries; dept.ils; faculty_collection

Readings About Children's Literature. - Robinson, Evelyn Rose (D. McKay Co., 1966)
Keywords: Books and reading; Children's literature; History and criticism; Children; dept.ils; faculty_collection

An Analysis of School Library Resources in Connecticut as Compared to National Standards, 1960-1961. - Prostano, Emanuel T. (University Microfilms, 1962)
Keywords: Connecticut; School libraries; dept.ils; faculty_collection

Symposium on Cooperative Efforts in Information Processing. Introduction - Schlessinger, B.S. (Journal of Chemical Documentation, 1973)
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils

The Amount of Reading Material in Book Form Printed Yearly in the USSR and the USA - Vebra, G.I. (Libri, 1973)
1 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Teaching scientific literature in the small college and university - Powell, A.; Schlessinger, B.S. (Journal of Chemical Education, 1971)
5 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Symposium on Functions and Contributions of the Industrial Information Center - Schlessinger, B.S. (Journal of Chemical Documentation, 1971)
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Trigant burrow and robert mearns yerkes the men and their papers - Stark, B.P. (Behavioral and Social Sciences Librarian, 1986)
Trigant Burrow and Robert Mearns Yerkes were two important behavioral scientists whose papers have recently been processed in Manuscripts and Archives, Yale University Library. Burrow was a pioneer American psychoanalyst and initiator of group analysis, while Yerkes was a prominent psychologist who is best known for his intelligence testing experiments in World War I and his studies of primate behavior. The paper discusses the lives and careers of both men; the research value of the two collections; the processing, arranging, and describing of the papers; and concludes with thoughts on access and the importance of finding aids to researchers and the institution that produces them. © 1986 by The Haworth Press, Inc.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils

The impact of local tape databases on the library: The M(I)das touch - Bakowski, V.B.; Moeckel, L.E. (Online (Wilton, Connecticut), 1990)
There is no abstract available for the item entitled The impact of local tape databases on the library: The M(I)das touch.
Keywords: dept.ils; ⛔ No DOI found

Planning more powerful ways to deliver information to the desktop - Dykman, E.K. (Online (Wilton, Connecticut), 1996)
Keywords: dept.ils; ⛔ No DOI found

The information quest as resolution of uncertainty: Some approaches to the problem - Sieving, P.C. (Information Seeking and Communicating Behavior of Scientists and Engineers, 1991)
The ideal user of scientific and technical information: shall we design one? The positive personality traits one would wish for in a spouse would do nicely for a start: patient; thoughtful; caring; able to see our (the librarians') virtues through the fog of early-morning not yet-wakefulness or late evening exhaustion; able to communicate needs and wants clearly and without a lot of emotional overtones; willing to work hard to obtain desired results; and apprecia tive of what We (librarians) do. Add to this other talents which, while useful, are less often associated with marriage: the ability to understand and retain complex organizational details; patience with less-than-perfect systems; an intuitive understanding of how information is organized; and a sense of how best to cope with the inter-face between the deluge of possible information resources and the limited needs of one particular user (not to mention limited capacities for retaining and controlling that information flood once the gates are open). © 1991 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: Inf. Seeking and Communicating Behavior of Scientists and Engineers
Keywords: dept.ils

Training the end user: The stanford university medical center experience - Linder, G.A.; Lenon, R.A.; Su, V.; Wible, J.G.; Stangl, P. (End User Searching in the Health Sciences, 1986)
The Lane Medical Library staff, working with a physician at Stanford University Medical Center, has developed a successful end user MEDLINE training program. 80th DIALOG and the National Library of Medicine’s (NLM) MEDLARS system are taught. Upon completion of the NLM course, students are eligible to receive academic credit and an NLM password. Several factors are identified as having been crucial to this success: (1) a strong working alliance between library staff and an enthusiastic physician, (2) early and ongoing support from influential leaders in the medical center, (3) minimization of barriers confronting potential end user searchers, and (4) strong emphasis on demonstration and hands-on practice. Costs and personnel support to achieve and maintain the program are discussed, and future plans outlined. © 1986 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: End User Search. in the Health Sciences
Keywords: dept.ils

Using the Computer for Library Random Sample Selection - Heinritz, FJ (College & Research Libraries, 1979)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1979GY06400008
Keywords: dept.ils

Decision Tables - Tool for Librarians - Heinritz, FJ (Library Resources & Technical Services, 1978)
tex.unique-id: ISI:A1978EM07600004
Keywords: dept.ils; ⛔ No DOI found

Recommended Procedures for Internal Financial Auditing of University-Libraries - Kurth,wh, Zubatsky,ds - Heinritz, FJ (College & Research Libraries, 1978)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1978EJ86000025
Keywords: dept.ils

Rate of Growth for Library Collections - Heinritz, F (College & Research Libraries, 1974)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1974S674800002
Keywords: dept.ils

Analysis and Evaluation of Current Library Procedures - Heinritz, FJ (Library Trends, 1973)
tex.unique-id: ISI:A1973P828100006
Keywords: dept.ils; ⛔ No DOI found

Systematic Analysis of University Libraries - Application of Cost-Benefit Analysis to Mit Libraries - Raffel,ja and Shishko,r - Heinritz, FJ (Library Resources & Technical Services, 1970)
tex.unique-id: ISI:A1970H282100022
Keywords: dept.ils; ⛔ No DOI found

Theory and Practice in American-Medicine - Historical Studies from Journal of History of Medicine and Allied Sciences - Brieger,gh - Triolo, VA (Isis, 1978)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1978FN05600029
Keywords: dept.ils

Continuing-Education in Online Searching - Instructional Module for Special Librarians - Triolo, VA; Regazzi, JJ (Special Libraries, 1978)
tex.unique-id: ISI:A1978EW38300005
Keywords: dept.ils; ⛔ No DOI found

Big-City Police - Fogelson,rm - Levy, BN (Library Journal, 1977)
tex.unique-id: ISI:A1977DZ57800179
Keywords: dept.ils; ⛔ No DOI found

History of Public-Library in Brunswick, Maine - Helmreich,lr - Libbey, DC (Journal of Library History Philosophy and Comparative Librarianship, 1977)
tex.unique-id: ISI:A1977EC67200018
Keywords: dept.ils; ⛔ No DOI found

So Thats the Reason - Perrins, BC (RQ, 1967)
tex.unique-id: ISI:A1967ZY24300006
Keywords: dept.ils; ⛔ No DOI found

Myths, misconceptions and mistakes in collection development - Yesner, Bernice L. (Collection Management, 1985)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00224 tex.type: [object Object]
Keywords: dept.ils

Librarians Agreements - Bargaining for a Heterogeneous Profession - Weatherford,jw - Kusack, JM (Journal of Academic Librarianship, 1989)
tex.unique-id: ISI:A1989AJ83900012
Keywords: dept.ils; ⛔ No DOI found

Taken aback - Kusack, J (Wilson Library Bulletin, 1987)
tex.unique-id: ISI:A1987K534200002
Keywords: dept.ils; ⛔ No DOI found

Output measures and library space planning - Lushington, N. (Library Trends, 1987)
This article suggests that over the next decade library performance measures - such as output measures - can become the basis for library space planning programs that will determine the quantity and relative location of user hierarchies for each type of public service.
Keywords: dept.ils; ⛔ No DOI found

A longitudinal study of emotion expression and personality relations in early development - Abe, J.A.A.; Izard, C.E. (Journal of Personality and Social Psychology, 1999)
To investigate emotion expression and personality relations, the authors coded infants' full-face and component positive and negative expressions during Episodes 4 through 8 of the strange situation procedure at age 18 months and obtained maternal ratings of the 5-factor model of personality when children were 3.5 years old. Full-face negative expression was directly related to Neuroticism and inversely related to Agreeableness and Conscientiousness. By contrast, component positive expression showed the exact opposite pattern of relations. Full-face positive expression was positively correlated with Extraversion and Openness to Experience. These findings indicate that full-face and component expressions may index different intensities of emotions. Emotion expression and personality relations were not mediated by the security of attachment continuum or the emotional reactivity dichotomy derived from the attachment subclassifications.
58 citations (Crossref) [2023-10-31]
Keywords: *Emotions; *Personality; Age Factors; Child; Preschool; Emotions; Female; Humans; Longitudinal Studies; Male; Personality; age; article; dept.ils; dept.psy; emotion; female; human; longitudinal study; male; personality; preschool child

The developmental functions of emotions: An analysis in terms of differential emotions theory - Abe, J.A.A.; Izard, C.E. (Cognition and Emotion, 1999)
A substantial body of theoretical literature testifies to the evolutionary functions of emotions. Relatively little has been written about their developmental functions. This article discusses the developmental functions of emotions from the perspective of differential emotions theory (DET; Izard, 1977, 1991). According to DET, although all the emotions retain their adaptive and motivational functions across the lifespan, different sets of emotions may become relatively more prominent in the different stages of life as they serve stage-related developmental processes. In the first section, we present a brief overview of relevant aspects of the theory. In the second section, we discuss how emotions play a central role in helping the individual achieve developmental milestones and tasks during four major periods of life: Infancy, toddler through preschool years, middle to late childhood, and adolescence. The underlying thesis of this article is that emotions play a central role in stimulating social cognitive attainments at each stage of development. © 1999 Psychology Press Ltd.
69 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Knowledge, concepts, and categories. - Brown, ME (Library & Information Science Research, 1999)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000079397400012
Keywords: dept.ils

Book Review: Electronic publishing and libraries. Planning for the impact and growth to 2003 - Brown,DJ - Brown, Mary E (Journal of the American Society for Information Science, 1997)
0 citations (Crossref) [2023-10-31] OCLC: 4650537768 Citation Key Alias: lens.org/107-477-196-608-69X, pop00100
Keywords: book.review; dept.ils

By any other name: Accounting for failure in the naming of subject categories - Brown, Mary E (Library & Information Science Research, 1995)
Research shows 65-80% of subject search terms fail to match the appropriate subject heading and one-third to one-half of subject searches result in no references being retrieved. In a cross-sectional study, 82 students (3rd grade through college) were presented complex concepts in a naming task. Concreteness, complexity, and syndeticity contributed significantly in explaining match-failure and predicting match-success. The likelihood of match-success following an initial failure is improved by manipulating the values of these three properties. Developmental trends which worked against match-success were observed. It is suggested that match-failure is a consequence of developmental naming patterns and that these patterns can be overcome through the use of metacognitive naming skills.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-254-372-457-138 tex.type: [object Object]
Keywords: dept.ils

To see or not to see - A study of video collection censorship in american public-libraries - Vroman, Deborah L. (RQ, 1995)
Citation Key Alias: vanfleetCurrentIssues1995 tex.unique-id: [object Object]
Keywords: dept.ils; ⛔ No DOI found

The information environment - a reader - walker,g - Kusack, J (Library Quarterly, 1993)
tex.unique-id: ISI:A1993KX91900016
Keywords: dept.ils; ⛔ No DOI found

A decision model for technical journal deselection with an experiment in biomedical communications - Triolo, Victor A; Bao, Dachun (Journal of the American Society for Information Science, 1993)
This report proposes a paradigm for technical journal deselection based on the Bradford Law of distribution, with a demonstration in biomedical communications illustrating various statistical derivations. The model employs the following operational prescriptives: (1) identification of fractional productivities in journal collections; (2) probability predictions for making successful retrievals of relevant items in any given productive fraction; (3) utilization by journal source language and origin; and (4) estimates of cost-efficiencies of searches made in print and machine-readable versions of serial publications. The results suggest that in approximately two out of three trials successful searches ('hits') are likely to be made in a `critical' core of any technical subject collection. The highest probability for retention resides in this portion, about 20% of the publications. We infer that substantial amounts of the remaining publications are candidates for deselection since their information content, as needed, may be captured more cost-effectively through electronic retrieval and document delivery access.
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1993KR97500003, lens.org/020-062-823-091-476 tex.type: [object Object]
Keywords: dept.ils

The light at the end of the carpal-tunnel - Kusack, JM (Library Journal, 1990)
tex.unique-id: ISI:A1990DN77000020
Keywords: dept.ils; ⛔ No DOI found